Analysis Modulation Formats in DWDM Transmission System - Li Li; WEI Jian-yi; LI Hong-an; ZHANG Xiu-tai (Institute of Advanced Engineering and Science, 2013)
In modulation and demodulation methods of the optical Differential Quadrature Phase Shift Key (DQPSK) and the different modulation formats including nonreturn-to-zero(NRZ), return-to-zero (RZ), carrier-suppressed return-to-zero(CS-RZ) are introduced, studying the different optical signals in the 40Gb/s high speed transmission system. The system is simulated in 200km optical fiber by way of dispersion compensation. It is showed that the ability of anti-dispersion and anti-PMD (Polarization Mode Dispersion) is better in the CS-RZ-DQPSK modulation format, and this format has the smallest eye-opening penalty (EOP) with a wider range of power into the optical fiber. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1800